Modern organizational structures, and the possibility of their adaptation in the ﬁeld of public administration - E V Lylova (RUDN Journal of Public Administration, 2018)
The article is devoted to the review of modern types of organizational structures through the prism of their practical application by both commercial structures and public administration bodies. Modern types of organizational structures provide great opportunities to achieve the goals of diﬀerent levels. In general, the trend of development of organizational structures is reduced to the predominance of a set of highly organized teams on the principle of horizontal management as opposed to the hierarchy of mechanistic organizational structures. The author emphasizes that there is no single correct, the most ideal type of organizational structure suitable for all organizations, regardless of production or service technology, organizational and legal form, strategy and operating conditions. First of all, for modern organizations it is important to adapt to the changing factors of the environment and the choice of the optimal organizational structure, taking into account the speciﬁcs of the activity. The requirements of the citizens to the quality of services and management functions are changing, the requirements of the world community to the implementation of public administration are also constantly growing - all this makes changes in the structure of public administration. This article attempts to explore the possibility of adapting new types of structures in the ﬁeld of public administration, which is committed to the concept of Good Governance.